Evaluation and Justification of RFID Implementation In IRAN Commercial Port's Container Supply Chain (Case Study: Bushehr Port) - Shahriar Mohammadi; Sedigheh Ardast (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2011)
Simultaneous with port's development and complexity in transportation processes, a number of problems have occurred in global supply chain. Nowadays, new technologies are used as a flexible solution to control quality of services and manage port's processes. One of the most effective existing technologies that can be used for container transportation is RFID technology. The most important benefit of RFID technology is the automation of processes through providing decision support systems based on real time and accurate data. This study follows an efficient RFID-Based model to improve port's container transportation. According to Literature review and available academic models, the port's RFID system cycle has been designed and a model has been proposed. This model has used the internal experience and the result of the initial site has been surveyed. By understanding the conceptual variables in the model and analysis of questionnaire's data and obtaining RFID and port expert's ideas, the final model has been presented. According to the study, the proposed model is believed to be efficient for Bushehr port's and has positive effect on security, speeding, Transparency and container's processes visibility and can be used as a pattern for other ports.